Triphala Described as an Antidiabetic Agent in Ayurveda Treatises: A Review - Reddy, K. R. C. (Asian Journal of Pharmaceutics (AJP), 2018)
Triphala is a well-known traditional ayurvedic formulation which is most commonly used to tone up and support the normal functioning of the bowel. Many traditional compounds containing Triphala as an ingredient, is found to be useful in the treatment of several kinds of ailments and diabetes is among one of them. Triphala has been described elaborately in Ayurveda for the treatment of Prameha (diabetes). In this present paper, an attempt has been made to summarize the antidiabetic potential of Triphala as a whole as well as the impact of individual drugs of Triphala. In present paper antidiabetic potential of this formulation is complied. In, Charaka Samhita 7 (30.4%), Sushruta Samhita 4 (17.4%) Astanga Samgraha 2 (8.7%), Vrinda Madhav 4 (17.4%), Gada Nigraha 4 (17.4%), and Chakradatta 2 (8.7%) formulations are described which possess Triphala as ingredient for antidiabetic action. Triphala has been used widely in different dosage forms. 1 formulation in the form of Swaras/rasa (4.3%), 4 as Churna (17.4%), 13 as Kwath/Kashaya (57.0%), 2 as Gutika/Guggulu (8.7%), 1 as Kshaar (4.3%), and 2 in the form of Avasa and Arishta (8.4%).